Mobile Application for Training of Foreign Students with Gamification Techniques and Speech Recognition Technology - Nisaul Barokati Seliro Wangi; Madekhan Madekhan (EDUTEC : Journal of Education And Technology, 2019)
The purpose of this research is to produce a mobile learning product that uses gamification techniques and valid speech recognition technology as a source of learning and is effective for training the pronunciation of foreign students. This type of research is a development research that uses the Lee & Owens model and is validated by 1 media expert, 1 material expert and 1 gamification learning design expert. The results of this study indicate that this application is valid and can be used for learning, students successfully complete the material, practice questions and reach the specified learning standards.